Pengembangan Aplikasi Web Layanan Sosial Masjid Jami At Taubah Juanda Menggunakan Framework Laravel - Ramadhani, Syifa Sukma; Panji, Krisna; Wibowo, Edi (DBESTI: Journal of Digital Business and Technology Innovation, 2025)
The development of information technology has influenced various aspects of life, including the administrative management of mosques. A web based social service and assistance application was developed to support the Mosque Management Board (DKM) and neighborhood leaders (RT) in managing data related to zakat, orphans, and qurban registrations. The system was developed using the Laravel framework and the waterfall software development methodology. Its main features include the management of zakat data, orphan records, and qurban registration through dedicated dashboards for Admin and RT roles. Black box testing confirmed that all system functionalities work properly. Furthermore, User Acceptance Testing (UAT) achieved a score of 87.5%, categorized as "very good" based on the average likert scale score. Therefore, the application is considered feasible and acceptable for end users.